Case Report: Congenital Perineal Lipoma Associated With Additional External Genitalia Anomalies - Francesca Tocchioni; Chiara Caporalini; Annamaria Buccoliero; Flavio Facchini; Marco Ghionzoli; Francesco Morini (Frontiers Media S.A., 2022)
Perineal lipoma is an uncommon congenital benign tumor sometimes associated with genitourinary or anorectal malformations. Accessory scrotum and accessory labioscrotal fold are infrequent features, often concurrent with perineal tumors. We describe a single institution experience with three consecutive cases of perineal lipoma associated with external genital anomalies, and a literature review.